Kesadaran Hukum Pelaku Usaha Kedai Kopi Terkait Label Halal Pada Jasa Penjualan Minuman Kopi Di Kota Malang - Kartika, Ari Purwita (NOVUM : JURNAL HUKUM, 2021)
Sales services for coffee in coffee shops according to the Halal Product Guarantee Law must be labeled as halal. Inclusion of a halal label made by the owner of Robusto Coffee, owner of Lupa Lelah and owner of Jali Merah Koffie is the obligation of business actors to provide true, clear and honest information regarding the condition of regulated goods and or services as regulated in the Consumer Protection Law. This study aims to analyze the awareness of coffee shop business actors towards the inclusion of halal labels on coffee shop sales services and to analyze the URAIS field of the Ministry of Religion of East Java Province as the Halal Certification Service Coordinator. The research method used is juridical empirical by using data study techniques through observation and interviews. The research data analysis technique was descriptive analytical. Based on the high and low level of legal awareness, 3 (three) coffee shop business actors in this study do not have legal awareness because the four indicators that affect legal awareness are not fulfilled. The cause of legal awareness of 3 coffee shop business actors is due to education and age factors. In addition to education and age factors, business actors are not aware of the lack of socialization from the URAIS Division of the Ministry of Religion of East Java Province as the East Java Province Halal Certification Service Coordinator and currently supervision is being carried out by the Head of the URAIS Section as the Coordinator of Halal Certification Services for coffee shop owners who are not has halal certification and halal label drinks on coffee sales services in Malang City by means of preventive and repressive supervision.